Statins are associated with better outcomes after carotid endarterectomy in symptomatic patients. - Kennedy, J; Quan, H; Buchan, A; Ghali, W; Feasby, T (2005)
BACKGROUND AND PURPOSE: Statins have been associated with a reduction in mortality from noncardiac surgery. This study aimed to determine whether statin use on admission to hospital for carotid endarterectomy was associated with a reduction of in-hospital adverse outcomes. METHODS: Data describing patient characteristics, surgical indication, statin treatment, and in-hospital outcomes of death, ischemic stroke or death and cardiac outcomes were collected from a chart review of all patients (3360) undergoing carotid endarterectomy in Western Canada from January 2000 to December 2001. Outcomes of patients on statins versus those not on statins were compared using logistic regression to account for differences in patient characteristics, and propensity score methods to account for factors influencing patient allocation to statins. RESULTS: Eight hundred and fifteen of 2031 symptomatic patients and 665 of 1252 asymptomatic patients were on a statin at the time of hospital admission. Statin use by symptomatic patients was associated with reduced in-hospital mortality and in-hospital ischemic stroke or death, but not in-hospital cardiac outcomes (adjusted odds ratio 0.25 [CI, 0.07 to 0.90], 0.55 [CI, 0.32 to 0.95], 0.87 [CI, 0.49 to 1.54], respectively). The improvement in outcomes was robust when tested using propensity score matching. This association was not seen in asymptomatic patients on statins (adjusted odds ratio, in-hospital mortality 0.54 [CI, 0.13 to 2.24]; in-hospital ischemic stroke or death 1.34 [CI, 0.61 to 2.93]; in-hospital cardiac outcomes 1.37 [CI, 0.73 to 2.58]). CONCLUSIONS: These findings are suggestive of a protective effect of statin therapy in symptomatic patients pre-treated at the time of carotid endarterectomy, though this needs confirmation in a randomized controlled trial.